Not All That Glitters Is Gold: The Paradox of CO-dependent Hydrogenogenesis in Parageobacillus thermoglucosidasius - Aliyu, Habibu; de Maayer, Pieter; Neumann, Anke (Frontiers in Microbiology, 2021)
The thermophilic bacterium Parageobacillus thermoglucosidasius has recently gained interest due to its ability to catalyse the water gas shift reaction, where the oxidation of carbon monoxide (CO) is linked to the evolution of hydrogen (H2) gas. This phenotype is largely predictable based on the presence of a genomic region coding for a carbon monoxide dehydrogenase (CODH - Coo) and hydrogen evolving hydrogenase (Phc). In this work, seven previously uncharacterised strains were cultivated under 50% CO and 50% air atmosphere. Despite the presence of the coo – phc genes in all seven strains, only one strain, Kp1013, oxidises CO and yields H2. The genomes of the H2 producing strains contain unique genomic regions that code for proteins involved in nickel transport and the detoxification of catechol, a by-product of a siderophore-mediated iron acquisition system. Combined, the presence of these genomic regions could potentially drive biological water gas shift (WGS) reaction in P. thermoglucosidasius.